Persepsi Keluarga Nelayan terhadap Pendidikan Anak - Dewi, Raysita; Sunarti, Vevi (Penerbit Aksara Rentaka Siar (ARS), 2019)
This research was motivated by the perception of fishermen families in their children’s education. This type of research is quantitative with a descriptive method. The sampling technique in this study is the random sampling method. The population is a family head of 30 people. The sample in this study were 30 family heads. Data collection tools are interviews. The results of the study show that (1) The perception of fishermen’s family in terms of efforts to fulfill the wishes of the child, (2) The perception of fishermen’s family in terms of aspects supporting the child’s achievement.